"Pull;" the Active Use of Dissonance. An IPA Pearl to Show Emotion Management in Action. Issue 4 (24th December 2020) - Vicary, Sarah
Abstract : This article explores emotion management of mental health social workers when undertaking a statutory function. Using data from a larger study of the Approved Mental Health Professional (AMHP), its aim is to explore a role that embodies a policy (both literally and metaphorically) concerning the distribution of professional responsibilities. Using the methodological approach Interpretative Phenomenological Analysis (IPA), this article explores the psychological and emotional experiences of participants from their own perspective. Data were collected from twelve AMHPs of three different non-medical backgrounds through a semi-structured interview that included the opportunity for each participant to draw and describe a Rich Picture of their experiences as AMHPs. Through one pearl, a small piece of data emerging form the larger corpus, AMHP work is shown to involve an active use of dissonance providing new insights into the enactment of mental health work and the role played by emotion. "Pull", refers to the active use of dissonance; the recognition and use of seemingly contradictory emotions that, crucially, co-exist. This article argues that current dialogue ignores the advanced management of emotion in role accomplishment and the value of AMHPs. The use of drawing alongside discussion of it, underpinned by IPA, has given rise to the pearl, "Pull", and its interpretation the active use of dissonance.